Preface of the 2nd International Electronic Conference on Processes (ECP 2023) - Giancarlo Cravotto; Dariusz Dziki; Krist V. Gernaey (Engineering Proceedings)
The 2nd International Electronic Conference on Processes: Process Engineering—Current State and Future Trends (ECP 2023) was hosted online from 17 to 31 May 2023 [...]